Burnout and Physical Activity as Predictors of Job Satisfaction Among Peruvian Nurses: The Job Demands-Resources Theory - Rafael Romero-Carazas; Robinson Bernardino Almanza-Cabe; Vidnay Noel Valero-Ancco; Antony Paul Espíritu-Martínez; Roque Juan Espinoza-Casco; Luzmila Lourdes Garro-Aburto; Alberto Miguel Vizcarra-Quiñones; Celfa Mónica Samaniego-Montoya; María Isabel Denegri-Velarde; Freddy Antonio Ochoa-Tataje (SAGE Publishing, 2024)
Background: The Job Demands-Resources (JD-R) theory suggests that an imbalance between job demands and available resources can lead to burnout, negatively affecting job satisfaction. Physical activity is recognized for its positive effects on psychological well-being and could play a crucial role in mitigating burnout and improving job satisfaction, especially in high-demand professions such as nursing. Objective: This study investigates the relationship between burnout, physical activity, and job satisfaction in Peruvian nurses, using the JD-R theory as a theoretical framework. Methods: A cross-sectional and explanatory analysis was conducted on a sample of 420 Peruvian nurses, using a Structural Equation Modeling (SEM) design to analyze the relationships between burnout, physical activity, and job satisfaction. The instruments included the Ultra-Short Burnout Measure (IUB), the General Job Satisfaction Scale NTP 394, and the International Physical Activity Questionnaire (IPAQ). Results: The findings showed a significant negative correlation between burnout and physical activity (β = −.40, P  < .001) and between burnout and job satisfaction (β = −.46, P  < .001). Physical activity exhibited a significant positive correlation with job satisfaction (β = .22, P  < .001). Moreover, mediation analysis confirmed that physical activity mediates the relationship between burnout and job satisfaction (β = −.106, P  < .001). Conclusions: The findings emphasize the importance of physical activity as a mediator in the relationship between burnout and job satisfaction among Peruvian nurses, highlighting the need to promote physical activity as a strategy to improve workplace well-being. It is suggested that enhancing access to and promotion of physical activity could mitigate the effects of burnout and improve job satisfaction, which is essential for the quality of care and the well-being of nursing staff. These findings underscore the need for organizational and public health strategies that promote a healthy work environment and balance between the demands and resources available.